(untitled) (Revista Electrónica REDINE, 2018)
This study is framed in an investigation of descriptive field, the same was to describe the use of ITC for teaching biotechnology. This research is focused on the constructivist theory supported on technological theory .The subjects of this study were composed of thirty (30) teachers who teach the subject of Biology. . The phase of the study was conducted primarily by the diagnosis is performed by applying an instrument with its evaluation by experts in the subject proposed. In other reliability was performed by calculating the Alpha Cronbach coefficient to determine that the instrument is homogeneous, uniform, consistent and reliable. The analysis results indicate that there is very high need for incorporating ITC for teaching biotechnology.